Sudden Unexpected Death in a Child with Vomiting and Diarrhea due to Intracranial Mass Lesion - Esra Betül Akkoyun; Sena Cantaş Örsdemir; Okşan Derinöz (Galenos Yayinevi, 2017)
Nausea and vomiting are common sequelae of a multitude of disorders that can range from mild to severe conditions. Intracranial mass lesions can occasionally present with vomiting followed by acute neurological deterioration and sudden death, although they are usually accompanied by ongoing neurological symptoms. We aimed to report an unusual presentation of an intracranial mass resulting in death to increase awareness among pediatric emergency physicians. A previously healthy 15-month-old boy presented to the pediatric emergency department (PED) with nausea, vomiting and diarrhea. He did not have any symptom of a neurological disorder. He acutely deteriorated, developed cardiopulmonary arrest and was intubated. His cranial computed tomography showed dilatation of the third and the lateral ventricles caused by a 3x4x2 cm tumor in the posterior fossa with an evidence of hemorrhage in the tumor with minimal tonsillar herniation. An emergent extra-ventricular drainage was performed to relieve elevated intracranial pressure. He did not show any improvement and died 9 hours after admission. Common symptoms in PED like nausea and vomiting are mostly due to benign etiologies such as gastroenteritis. One should always keep in mind that there may be an underlying intracranial pathology and further investigation should not be delayed.